Compressive strength and microstructural analysis of recycled coarse aggregate concrete treated with silica fume. (6th June 2022) - Zhu, Lihua; Ning, Qiujun; Han, Wei; Bai, Leilei
Highlights: RCA was treated with SFC paste. The slump and compressive strength of TRCAC was improved significantly. The failure mode and compressive strength of TRCAC were similar to those of CC. The ITZ thickness of RAC was reduced, and the microstructure was improved. Abstract: Recycled coarse aggregate 1 (RCA) was treated with silica fume cement 2 (SFC) paste. Subsequently, specimens of two types of concrete were prepared: one with treated RCA 3 (TRCA) and another with natural coarse aggregate 4 (NCA) based on conventional concrete 5 (CC) mixture designs. The slump, cubic, and prism compressive strengths of the two concretes were compared and analyzed. Moreover, the microstructures of these two concretes were qualitatively analyzed using scanning electron microscopy 6 (SEM) and energy-dispersive spectroscopy 7 (EDS). The results showed that the mechanical performance of TRCA concrete 8 (TRCAC) was improved significantly. The enhanced strength of this recycled aggregate concrete 9 (RAC) is mainly due to the incorporation of silica fume, which can improve the quality of RCA and reduce the thickness of the interfacial transition zone 10 (ITZ) of RAC.